2020
DOI: 10.1111/jerd.12623
|View full text |Cite
|
Sign up to set email alerts
|

Effect of surface treatment on the retention of zirconia crowns to tooth structure after aging

Abstract: Objective: To evaluate the effect of different surface treatments on the retention between zirconia crowns and tooth structure after in vitro aging. Materials and methods: Human third molars (n = 44) received crown preparations and CAD/CAM zirconia crowns were manufactured. Specimens were divided into two groups: no aging, control (NAC, n = 11) or aging (A, n = 33). NAC were bonded with universal adhesive (UA). Aged specimens were divided into three subgroups (n = 11) according to surface treatment: Control: n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 61 publications
0
10
0
Order By: Relevance
“…The search revealed 18 studies on bonding to 5Y‐TZP zirconia 86,95,96,98–111 . The three types of surface pretreatment methods were applied: mechanical, through alumina and glass‐bead APA; chemical–mechanical, through TBS, lithium disilicate glass–ceramic coat, and plasma treatment; and chemical, through piranha acid etch solution and hot chemical etching (Table 2).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The search revealed 18 studies on bonding to 5Y‐TZP zirconia 86,95,96,98–111 . The three types of surface pretreatment methods were applied: mechanical, through alumina and glass‐bead APA; chemical–mechanical, through TBS, lithium disilicate glass–ceramic coat, and plasma treatment; and chemical, through piranha acid etch solution and hot chemical etching (Table 2).…”
Section: Resultsmentioning
confidence: 99%
“…It exerts dual functionality by increasing the silica content on the zirconia surface and roughening it, thereby creating a conducive surface for silanization that promotes chemical affinity to resin cements 50,139–141 . Application of an MDP‐based primer on TBS‐treated zirconia resulted in durable bond strengths 99,100,106 and failure modes were predominantly mixed (Table 2). All MDP primers in the identified studies incorporate silane molecules in their chemical composition (Table 2).…”
Section: Discussionmentioning
confidence: 99%
“…Both the coated samples showed similar retention strength of 4 MPa, and control had 0.8 MPa strength. [35] Cochlear implant Coating of poly(4-hydroxybutyrate) with brain derived neurotrophic factor in the presence of disuccinimidyl suberate (DSS).…”
Section: Biomaterials Surface Treatments Results Referencesmentioning
confidence: 99%
“…Another study found pre-treatment of zirconia with hot acid mixtures (69% nitric acid and 48% hydrofluoric acid) after air-borne particles abrasion enhanced the bond between zirconia and the resin cement, and the specimens revealed a wider distribution roughness which result in micromechanical retention and better bonding strength [35]. Furthermore, Monteiro et al [43] evaluated the impact of various pre-treatment methods after aging and concluded that, relative to air-borne particle abrasion, tribochemical silica coating did not offer extra retention for zirconia restorations.…”
Section: Discussionmentioning
confidence: 99%
“…Shear, tensile, microtensile or retention tests, are commonly employed to determine the bonding performance of a luting cement [37][38][39][40][41]. The retention test was employed by many researches, where the cemented restoration is subjected to axial dislodging forces till failure [39,42,43]. The purpose of this in-vitro investigation was to evaluate the influence of hot acids chemical pre-treatment and the cement type (Panavia SA cement (Kuraray Noritake Dental Inc., Okayama, Japan) plus and G-CEM LinkForce cement (GC America Inc., Chicago, IL, USA) on the retention of monolithic zirconia restoration.…”
Section: Introductionmentioning
confidence: 99%